Prevention of amblyopia in childhood traumatic cataract with intraocular lens implantation: a case report - Öge, İhsan; Öge, Fatma (The Turkish Journal of Pediatrics, 1987)
A five-year-old boy with traumatic cataract is presented who had undergone a combined anterior chamber lens implantation and the Nd:YAG laser posterior capsulotomy procedure. The patient was followed up for a period of 18 months. The young boy showed an improvement in visual acuity without any signs of complications. These results encourage further investigation into this procedure.
Keywords: trauma; cataract; implantation; intraocular lens